Esports fandom in the age of transmedia: the reception of the overwatch league - Tanja Välisalo (SHARE Press, 2021)
In our article, we analyse the ways audiences engage with Overwatch esports and construct their fan relationships. We situate our research into several intersecting theoretical frames. To understand how Overwatch esports audiences engage with the esports through different media and media related practices we apply the framework of transmedia studies in our examination. To better understand how meanings related to esports are constructed through these practices we also draw from research on fandom and fan engagement. We reflect these findings on earlier research on sports fandom and esports viewership, enabling us to identify how Overwatch esports communities relate to traditional sports communities. Our study reveals how esports is intertwined with the everyday lived reality of the esports audiences, and how meanings are constructed through (mediated) audience practices. Our article contributes to the study of esports transmedia and to the understanding of the similarities and differences of esports and sports audiences.